Bisma ki machli - Yasmin Mutasim Barjees; Yasmin Mutasim Barjees (Karachi: Children Publications)
"Bisma Ki Machli" is an engaging and heartwarming Urdu story for children, written with simplicity and charm. The book revolves around Bisma, a young and curious girl who develops a special bond with her pet fish. The story captures her joy, excitement, and sense of responsibility as she learns to care for her beloved pet. Through Bisma$1 (Bs experiences, the book imparts valuable lessons about empathy, kindness, and the importance of taking care of living beings. It also subtly teaches children about nature, responsibility, and the delicate balance of life. The narrative is filled with moments of innocence, curiosity, and emotional connection, making it relatable and enjoyable for young readers. "Bisma Ki Machli" is not just a delightful tale about a girl and her fish but also an educational journey that nurtures a sense of compassion in children. It is an excellent choice for parents and educators looking to introduce moral values through storytelling.s
Bisma Ki Machli is a delightful Urdu story that beautifully blends entertainment with moral lessons, making it an excellent read for children. The story revolves around Bisma and her pet fish, showcasing her journey of care, responsibility, and emotional connection with her aquatic friend. The book introduces young readers to the concept of empathy, the importance of nurturing relationships, and the responsibility that comes with caring for other living beings. Through simple language and relatable scenarios, it inspires children to appreciate the small wonders of nature and understand the significance of kindness and love. This story serves as a valuable resource for parents and teachers, offering an engaging way to teach important life lessons while fostering a love for reading in children.
Keywords: Curiosity; Life Lessons